Deliverance [videorecording (DVD)] - Boorman, John, 1933-; Voight, Jon, 1938-; Reynolds, Burt; Beatty, Ned; Cox, Ronny; Dickey, James (Warner Bros. Pictures : Distributed by Warner Home Video, 2007)
They left their troubles at the office. Left the wives and kids behind. Four men bound for the wilderness, for a great adventure--without their golf clubs. Lewis has talked his buddies Ed, Drew, and Bobby into going on a canoe trip down the Cahulawassee River, which is being soon to be dammed. It was the weekend they hoped for, but it turns out to be a weekend where the destruction of nature, macho posturing, conflict between city and country folk, and the dangerous disconnection of modern civilization from nature will loom entirely too large.